Antibacterial Activity of Keji Beling (Strobilanthes crispa) Ethanol Extract Using TLC – Bioautography - Junardin, Nurul Fadhillah; Nuryanti, Siska; Asmaliani, Ira (Journal Microbiology Science, 2024)
Antibacterials are compounds that inhibit the growth of bacteria that are harm humans. Keji Beling (Strobilanthes crispa) contains secondary metabolites such as saponins, flavonoids, terpenoids, polyphenols, and potassium. One part used in traditional medicine is the leaves which can treat various diseases. In this study, the ethanol extract of Keji Beling leaves was tested using TLC-bioautography This study tested the ethanol extract of Keji Beling leaves using TLC-bioautography. The examination begins with a screening for antibacterial activity against several pathogen bacteria, with results that inhibit the growth of Bacillus subtilis, Escherichia coli, Staphylococcus aureus, Staphylococcus epidermis, Pseudomonas aeruginosa, Streptococcus mutans, Salmonella typhii, Shygella dysenteriae, and Vibrio cholera. Test results using the TLC-bioautography method using n-hexane eluent: ethyl acetate (1: 2) found that the spots were active against bacteria Pseudomonas aeruginosa and Staphylococcus aureus Rf value 0.74 and bacteria Bacillus subtilis, Escherichia coli, Salmonella thypii, Staphylococcus epidermidis, Staphylococcus mutans, Shygella dysenteriae, Vibrio cholera with an Rf value of 0.83 The results of the identification of chemical components showed the presence of positive compounds belonging to the class of flavonoids and anthraquinones. The ethanol extract of keji beling leaves contains a class of flavonoid compounds that have the potential as antibacterial agents with an Rf value of 0.83